Transcriptomic and cellular decoding of regional brain vulnerability to neurogenetic disorders - Jakob Seidlitz; Ajay Nadig; Siyuan Liu; Richard A. I. Bethlehem; Petra E. Vértes; Sarah E. Morgan; František Váša; Rafael Romero-Garcia; François M. Lalonde; Liv S. Clasen; Jonathan D. Blumenthal; Casey Paquola; et al. (Nature Communications, 2020)
How neurodevelopmental disorder-associated risk genes are translated into spatially patterned brain vulnerabilities is unclear. Here, the authors show that disorder-specific patterns of neuroanatomical changes are aligned to brain expression maps of disease risk genes in healthy subjects.